Tantangan Pelaksanaan Pendidikan Inklusi di Sekolah Dasar Negeri 7 Trienggadeng Pidie Jaya - Mardhiah, Ainul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The implementation of inclusion education in Indonesia is not as easy as turning the palm of your hand, therefore inclusion education needs serious handling from both the government, schools, parents, and the community in general. This is also very much in line with the vision, mission and regulation of the Regent of Pidie Jaya number 29 of 2017 concerning the organizer of inclusive education in Pidie Jaya. So far, Pidie Jaya has 20 schools that provide inclusive education, one of which is SD Negeri 7 Trienggadeng. This study aims to find out the challenges of implementing inclusive education at SD Negeri 7 Trienggadeng Pidie Jaya. This research method uses a qualitative type of research with a case study approach. The data collection techniques carried out by the researcher are through observation, interviews and documentation. The research subjects consisted of the principal, special assistant teacher (GPK), and 1 classroom teacher. Based on the results of the study, it is known that the challenges faced by school principals in the implementation of Inclusion education at SD Negeri 7 Trienggadeng are; lack of human resources, lack of facilities and infrastructure, lack of cooperation between schools and parents, lack of community participation in the importance of inclusive education in schools